2022
DOI: 10.1108/ijchm-09-2021-1136
|View full text |Cite
|
Sign up to set email alerts
|

Fostering green service innovation perceptions through green entrepreneurial orientation: the roles of employee green creativity and customer involvement

Tuan Trong Luu

Abstract: Purpose Developing new green services is critical to a hospitality organization’s achievement of sustainable goals as well as competitive advantage. This study aims to unravel the mechanisms through which organizations with green entrepreneurial orientation (green EO) can foster green service innovation. Design/methodology/approach The data set for testing these mechanisms was garnered from employees and managers who worked in hotels based in an Asia-Pacific market. A multilevel analysis was conducted on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 135 publications
(213 reference statements)
0
35
0
Order By: Relevance
“…Actually, recent studies have already proposed constructs more or less related or overlapped with the concept of moral norm. Similar constructs such as meaningfulness of sustainable behavior and moral attitude (Luu, 2020), responsibility (Ahmed et al , 2021; Schwartz, 1977), green mindfulness (Kalyar et al , 2021) and green values (Raza and Khan, 2022) were all identified as useful mediators between green practice and sustainable behavior. Therefore, the current study along with these similar constructs indicated the direction and the values of studying moral norm as a mediator.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Actually, recent studies have already proposed constructs more or less related or overlapped with the concept of moral norm. Similar constructs such as meaningfulness of sustainable behavior and moral attitude (Luu, 2020), responsibility (Ahmed et al , 2021; Schwartz, 1977), green mindfulness (Kalyar et al , 2021) and green values (Raza and Khan, 2022) were all identified as useful mediators between green practice and sustainable behavior. Therefore, the current study along with these similar constructs indicated the direction and the values of studying moral norm as a mediator.…”
Section: Discussionmentioning
confidence: 92%
“…information asymmetry, product packing and corporate environmental responsibility) (Chang et al , 2021; Luu, 2020; Perrigot et al , 2021; Yang and Gao, 2021) and the human resources management practice/policies aspects (e.g. environmental management and green technology) (Ahmed et al , 2021; Aboramadan and Karatepe, 2021; Luu, 2022; Muisyo et al , 2022; Rehman et al , 2021; Kraus et al , 2020). What are the motivation elements of an individual, and how the effects of moral normal and anticipated emotions that are conducting sustainable behaviors were seldom examined in a sustainable context.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hackathons should be supported by decision makers such as businesses, R&D managers, or venture capitalists who invest in developing applications or ideas further. A further challenge concerns the adoption of hackathons by actors in the city's ecosystem and whether they fit in the smart city's entrepreneurial culture [45][46][47][48][49]. The results of this study indicate that hackathons are well accepted by stakeholders in the Thessaloniki municipality, especially developers.…”
Section: Hackathon For Service Innovation With Digital Platformmentioning
confidence: 88%
“…This is because the opinions of owners or managers Environmental performance in restaurants strongly influence how businesses execute environmental strategies and determine the outcomes of their decisions. Unlike manufacturing firms, service businesses, including restaurants require direct and close interactions with customers to validate their effort to protect the environment and to reinforce a positive image leading to enhanced performance (Luu, 2022). Therefore, restaurant owners or managers who are widely aware of environmental risks may be able to initiate pro-environment strategic actions to improve environmental performance.…”
Section: Restaurant Environmental Cognitionmentioning
confidence: 99%
“…To improve environmental performance, business managers must have an accurate understanding of the risk of environmental pollution (Begum et al, 2022). Business operators' EC is a starting point when the objective is to improve environmental performance (Luu, 2022). The service industry focuses on human resource management because the corporate image and reputation perceived by customers rely on management philosophy and leadership style (Raza and Khan, 2022).…”
Section: Restaurant Environmental Cognition and Environmental Perform...mentioning
confidence: 99%